Dissecting nuclear Wingless signalling: recruitment of the transcriptional co-activator Pygopus by a chain of adaptor proteins. - Staedeli, R.; Basler, K. (Mechanisms of Development, 2005)
Members of the Wingless (Wg)/Wnt family of secreted glycoproteins control cell fate during embryonic development and adult homeostasis. Wnt signals regulate the expression of target genes by activating a conserved signal transduction pathway. Upon receptor activation, the signal is transmitted intracellularly by stabilization of Armadillo (Arm)/beta-catenin. Arm/beta-catenin translocates to the nucleus, interacts with DNA-binding factors of the Pangolin (Pan)/TCF/LEF class and activates transcription of target genes in cooperation with the recently identified proteins Legless/BCL9 (Lgs) and Pygopus (Pygo). Here, we analyse the mode of action of Pan, Arm, Lgs, and Pygo in Drosophila cultured cells. We provide evidence that together these four proteins form a 'chain of adaptors' linking the NH2-terminal homology domain (NHD) of Pygo to the DNA-binding domain of Pan. We show that the NHD has potent transcriptional activation capacity, which differs from that of acidic activator domains and depends on a conserved NPF tripeptide. A single point mutation within this NPF motif abolishes the transcriptional activity of the Pygo NHD in vitro and strongly reduces Wg signalling in vivo. Together, our results suggest that the transcriptional output of Wg pathway activity largely relies on a 'chain of adaptors' design to direct the Pygo NHD to Wg target promoters in an Arm-dependent manner.